PENGARUH CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON EQUITY PADA PT. BANK MANDIRI (PERSERO) Tbk. PERIODE 2013-2024 - Nur Wantiningsih; Endang Nurita (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) on Return on Equity (ROE) at PT Bank Mandiri (Persero) Tbk. for the period 2013–2024. The method used in this research is a quantitative method with a descriptive and associative approach. The data source used is secondary data. The population consists of the financial statements of PT Bank Mandiri (Persero) Tbk. for the period 2013–2024. The sample is derived from the notes to the financial statements, balance sheets, and income statements of PT Bank Mandiri (Persero) Tbk. for the period 2013-2024. The results of the study indicate that the Capital Adequacy Ratio has a significant effect on Return on Equity, while the Loan to Deposit Ratio does not have a significant effect on Return on Equity. However, the study also shows that Capital Adequacy Ratio and Loan to Deposit Ratio simultaneously have a significant effect on Return on Equity.